Interleukin-10 exhibit dose-dependent effects on macrophage phenotypes and cardiac remodeling after myocardial infarction - Zhang, Jing J.; Rizk, Rodrigue; Li, Xiaoping; Lee, Brandon G.; Matthies, Mason L.; Bietz, Kennedy A.; Kim, Kang; Huard, Johnny; Wang, Yadong; Chen, William C. W. (Frontiers in Physiology, 2025)
IntroductionInterleukin-10 (IL-10) is a potent immunomodulatory cytokine widely explored as a therapeutic agent for diseases, including myocardial infarction (MI). High-dose IL-10 treatment may not achieve expected outcomes, raising the question of whether IL-10 has dose-dependency, or even uncharted side-effects from overdosing. We hypothesized that IL-10 has dose-dependent effects on macrophage (Mφ) phenotypic transition and cardiac remodeling after MI.MethodsUsing RAW264.7 monocyte models, we examined whether administering differential doses of exogenous IL-10 (0–1,000 ng/mL) perturbs classic M1 (pro-inflammatory) and M2 (anti-inflammatory) phenotypes of polarized Mφ or even alters the phenotypic transition of prospective M1 and M2 polarization. We then investigated the impact of single intramyocardial IL-10 administration on cardiac function, structure, and inflammation post-MI, using a mouse MI model.ResultsCompared with 0-ng/mL control, 250-ng/mL IL-10 had the strongest overall effects in decreasing M1 and increasing M2 phenotypes on polarized Mφ while ≥500-ng/mL IL-10 dampened M1 polarization and augmented native IL-10 secretion more effectively than low doses in vitro. Echocardiography revealed that the 250-ng group had consistently higher contractile function and lower left ventricular (LV) dilatation than the saline control over 6 weeks while ≥1,000-ng groups exhibited transient lower LV ejection fraction at 5 days post-MI in vivo. Moreover, different doses of IL-10 differentially modulated myocardial gene expression, phagocytic cell infiltration at the infarct, LV fibrosis, and revascularization post-MI, with some, but not all, doses exerting beneficial effects.DiscussionOur study suggested that IL-10 has an effective dose range on Mφ phenotypes, and intramyocardial IL-10 treatment may trigger cardioprotective or unwanted effects post-MI in a dose-dependent manner.